Stress Disorders Following Prolonged Critical Illness in Survivors of Severe Sepsis. Issue 6 (June 2015) - Wintermann, Gloria-Beatrice; Brunkhorst, Frank Martin; Petrowski, Katja; Strauss, Bernhard; Oehmichen, Frank; Pohl, Marcus; Rosendahl, Jenny
<x xml:space="preserve">Abstract</x> Objectives: To examine the frequency of acute stress disorder and posttraumatic stress disorder in chronically critically ill patients with a specific focus on severe sepsis, to classify different courses of stress disorders from 4 weeks to 6 months after transfer from acute care hospital to postacute rehabilitation, and to identify patients at risk by examining the relationship between clinical, demographic, and psychological variables and stress disorder symptoms. Design: Prospective longitudinal cohort study, three assessment times within 4 weeks, 3 months, and 6 months after transfer to postacute rehabilitation. Setting: Patients were consecutively enrolled in a large rehabilitation hospital (Clinic Bavaria, Kreischa, Germany) admitted for ventilator weaning from acute care hospitals. Patients: We included 90 patients with admission diagnosis critical illness polyneuropathy or critical illness myopathy with or without severe sepsis, age between 18 and 70 years with a length of ICU stay greater than 5 days. Interventions: None. Measurements and Main Results: Acute stress disorder and posttraumatic stress disorder were diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, criteria by a trained and experienced clinical psychologist using a semistructured clinical interview for Diagnostic and Statistical Manual of Mental Disorders. We further administered the Acute Stress Disorder Scale and the Posttraumatic Symptom Scale-10 to assess symptoms of acute stress disorder and posttraumatic stress disorder. Three percent of the patients had an acute stress disorder diagnosis 4 weeks after transfer to postacute rehabilitation. Posttraumatic stress disorder was found in 7% of the patients at 3-month follow-up and in 12% after 6 months, respectively. Eighteen percent of the patients showed a delayed onset of posttraumatic stress disorder. Sepsis turned out to be a significant predictor of posttraumatic stress disorder symptoms at 3-month follow-up. Conclusions: A regular screening of post-ICU patients after discharge from hospital should be an integral part of aftercare management. The underlying mechanisms of severe sepsis in the development of posttraumatic stress disorder need further examination.